Provider recommendation for HPV vaccination across Hispanic/Latinx subgroups in the United States - Paul L. Reiter; Michael L. Pennell; Glenn A. Martinez; Mira L. Katz (Taylor & Francis Group, 2021)
Healthcare provider recommendation is a key predictor of HPV vaccination among adolescents, yet little is known about how parents' receipt of a provider recommendation differs across Hispanic/Latinx subgroups in the United States. We analyzed data from the 2012-2016 National Immunization Survey - Teen on Hispanic/Latinx adolescent ages 13-17 (n = 16,335). Analyses used weighted logistic regression models. Overall, 62.6% of parents of Hispanic/Latinx females and 46.4% of parents of Hispanic/Latinx males reported that they had received a provider recommendation for HPV vaccination. Among parents of females, receipt of a provider recommendation ranged from 55.0% among Central Americans to 73.3% among parents of Puerto Ricans. Among parents of males, the range was from 44.5% among Mexicans and multi-subgroup males to 53.4% among Cubans. There were no differences across Hispanic/Latinx subgroups in adjusted models among either males or females (all p > .05). Among parents of females, provider recommendation was less common among those whose preferred language was Spanish for Central Americans and South Americans (both p < .05). Efforts are needed to improve provider communication about and recommendations for HPV vaccination among the Hispanic/Latinx population and to ensure the availability of language assistance services for individuals with limited English proficiency.